Arisan Online di Kota Sigli: Tinjauan dari Segi Hukum - Mariana Mariana (HEI EMA : Jurnal Riset Hukum, Ekonomi Islam, Ekonomi, Manajemen dan Akuntansi, 2024)
This research aims to understand the practice of online arisan and legal perspectives on online arisan practices among the community in Sigli City. The research method employed is qualitative, allowing the researcher to gain in-depth insights into the topic under study. In collecting data, the author utilized various approaches, including library research and field research methods. Research shows that online arisan in Sigli City has rapidly adopted platforms like WhatsApp, Facebook, and Instagram. Online arisan allows broad participation with high efficiency. Besides pooling funds, it strengthens social ties and offers opportunities for investments in descending or flat arisan schemes. From an Islamic law perspective, it's crucial to adhere to Sharia principles such as transparency, participant consent, and fair treatment. Proper documentation is key to resolving disputes like breach of contract or fraud.